Sinergi Dan Strategi Kebijakan Lintas Kementerian: Kasus Kelapa Sawit K2-I DI RIAU - Anwar, Khairul (Jurnal Kebijakan Publik, 2012)
Thisstudy aimed to explore the dynamic formulation of decentralization policies by taking the casemanagement policy palm plantations in Riau K2-I 2005-2010. The method used to achieve thisgoal is the use of modern political economy approach, which includes four phases, as describedin Frieden (1991). The results of this study found that: first, the formulation of policies on post-ministerial synergies of regional autonomy is determined by the changing patterns of interactionactor bureaucrats, businessmen, and politicians are increasingly dynamic. Second, the actorshave interests and clashing political freverensi. Third, the arena and the network used by aktrorLocal increasingly overlap.